Evidence in Primary Correspondence of Cognate in Indonesian and Madurese Language - Akhmad Sofyan; Agustina Dewi Setyari; Dewi Angelina (Master Program in Linguistics, Diponegoro University, 2019)
Cognate languages will have similarities and resemblances in sound systems that are manifested in the form of phonological correspondence. Indonesian language formed from Malay has a kinship relationship with the Madurese language. Relationships of these languages will certainly present many similarities. The method used to analyze the data in this paper is a comparative method, that is comparing the BI sound system and the BM sound system. The primary correspondence between the sound system of the Indonesian language and the Madurese language includes: (1) [i]/[I]>[ε], (2) [u]>[כ], (3) [a]>[â], (4) [w]>[b], (5) [t#]>[?], dan (6) [h]>[Θ].